(3TQM eTcdGJ TPhQ GdPgHs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI Yf eYfj bhdI aj OjhGfg GdJj de JSeM HeKdI dG bHdI hdG HYOI KdK GdeSN eG eYfj GdKdK bGd Udj Gddg Ydjg hSde djS aj bVGjG GdfLhe bVjI CUOb efg s
(3BNQgG (B:s
(3aEPG CNPJg aGWQM hRf KdGKI CLRGA Ydi LRA ef GdPgH hGVQHg VQHkG TOjOkG aEf GdOgf jZdX s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdcjejGA h GdWHjYjGJs